Utilization of Nylon-Based Eggshell Waste in the Making of Microfiltration Membranes for Reducing Metal Fe3+ - Krisna Yudha Syahputra; Malikhatul Hidayah; Wardatul Bahiyyah (Indonesian Journal of Chemical Science, 2023)
Eggshell waste can be used as an additive for membrane manufacture; one of the ingredients that can be utilized is CaO. CaO from duck eggshells can be extracted using a calcination process for 3 hours at 900℃. In the calcination results carried out by the FTIR test, Ca-O groups were formed at the group wave number of 478.62 cm-1. The membrane was prepared by adding the synthesized CaO in a nylon membrane, and the FTIR results showed that the 10%, 20%, and 30% nylon-CaO membrane was at wave number 444.56 cm-1, 444.61 cm-1, and 444.66 cm-1, which shows the Ca-O group. The application of the nylon-CaO membrane by carrying out the filtration process for Fe3+ metal ions, seen from the flux and rejection values of the addition of 30% CaO to the membrane, resulted in a flux value of 147.29 L/m2.hour and a rejection of 99.6%. The nylon-CaO membrane was also carried out by SEM-EDX-mapping analysis. It was seen that the 30% nylon-CaO membrane had a pore size of 2.77 μm which included an asymmetric microfiltration membrane that contained 0.46% mass Ca which was spread throughout the membrane